Long-Term Management of Refractory Vaginal Trichomoniasis Following Initial Metronidazole Treatment Failure: a Case Series - Maruki, Taketomo; Ishikane, Masahiro; Kurokawa, Masami; Kubo, Taketo; Miyazato, Yusuke; Ohmagari, Norio (Japanese journal of infectious diseases, 2025)
Guidelines for sexually transmitted infections recommend oral metronidazole (MNZ) as the first-line treatment option for vaginal trichomoniasis; however, cases of prolonged symptoms or post-treatment recurrence have been reported. This retrospective cohort study aimed to determine appropriate treatment strategies for refractory vaginal trichomoniasis. We reviewed the medical records of patients who tested positive for Trichomonas vaginalis (T. vaginalis) at the National Center for Global Health and Medicine between August 2011 and May 2023. Refractory vaginal trichomoniasis was defined as initial MNZ treatment failure. During the study period, nine cases of vaginal trichomoniasis were identified, six of which were refractory to treatment for T. vaginalis. Four patients were cured with a combination of oral and vaginal tinidazole (TNZ) therapy, one with oral TNZ, and one with two doses of MNZ. Possible causes of treatment failure include MNZ-resistant T. vaginalis, reinfection between partners, and infections of other sexually transmitted diseases. However, TNZ was effective, which suggests that MNZ-resistant T. vaginalis may have been the cause. MNZ resistance testing was not performed in this study; however, treatment with TNZ should be considered in cases of refractory vaginal trichomoniasis, possibly resulting from MNZ-resistant T. vaginalis.